A Fair Scheduling Algorithm to Improve Stability Region with Zero-Forcing Beamforming for a Multiuser MIMO Wireless Systems - Foronda, A.; Ohta, C.; Tamaki, H. (2007 4th International Symposium on Wireless Communication Systems, 2007)
Dirty paper coding (DPC) is a strategy to achieve the region capacity of multiple input multiple output (MIMO) downlink channels and a DPC scheduler is throughput optimal if users are selected according to their queue states and current rates. However, DPC is difficult to implement in practical systems. Then, zero-forcing beamforming (ZFBF) strategy has been proposed to achieve the same asymptotic sum rate capacity as that of DPC with an exhaustive search over the entire user set. And some suboptimal user group selection schedulers with reduced complexity based on ZFBF strategy (ZFBF-SUS) and proportional fair (PF) scheduling algorithm (PF-ZFBF) have also been proposed to enhance the throughput and fairness among the users, respectively. However, the fairness among the users and the throughput decrease if users queue length are different due to different users channel quality. Therefore, we propose a new fair scheduling algorithm with reduced complexity to improve the stability region based on ZFBF strategy (ZFBF-RC) and, at every time slot, the scheduling algorithm has to select some users based on user channel quality, user queue length and orthogonality among users.